Strategic Thinking and Performance of Small and Medium-Sized Dairy Processing Firms in Kenya - Joyce Muthoni Mbaya; Samuel Maina; Mary Namusonge (European Scientific Journal, ESJ, 2021)
The dairy sector plays a crucial role in economic growth and development of Kenya. However, many firms in the sector, especially the small and medium-sized, continue to face performance challenges such as competition from unregulated informal milk market, accessing markets and high industry barriers among others. A review of literature shows that the effect of strategic thinking on the performance of small and medium-sized dairy processing firms remains uncertain. This study sought to determine the effect of strategic thinking and performance of small and medium-sized dairy processing firms in Kenya. The study was anchored on the Leidtka Model. Positivism research philosophy was adopted. Descriptive and explanatory research designs were used. A census survey was conducted on all the small and medium-sized dairy processing firms in Kenya and primary data was collected. Descriptive statistics such as mean and standard deviation were used to explain data characteristics, while multiple regression was used to test the effect of the study variables on firm performance. The results showed that strategic thinking has a positive significant effect on the performance of small and medium-sized dairy processing firms in Kenya, thus it was perceived that strategic thinking aids creation of a path for what the firm wants to become through focusing on their intent, systems, timely thinking, intelligent opportunism, and hypothesis-driven research. The study contributes to the body of knowledge by filling contextual, empirical, and conceptual gaps identified earlier in literature and establishing a nexus of strategic thinking and performance of small and medium-sized dairy processing firms in Kenya. The study recommends that strategic thinking should be enhanced particularly by using research to inform their decision-making and practice quick decision-making to mitigate or exploit opportunities while thinking of possible solutions to unexpected challenges.